Significance of umbilical trocar size and intra‐abdominal pressure on postoperative pain after transabdominal preperitoneal repair for inguinal hernia. Issue 1 (28th May 2020) - Kinoshita, Shoichi; Ohyama, Takao; Kawaguchi, Chihiro; Ikeda, Naoya; Sho, Masayuki
Abstract: Introduction: Laparoscopic inguinal hernia repair is reported to be associated with lower postoperative pain than open repair. However, in the actual clinical setting, some patients experience relatively severe pain. This study aimed to elucidate surgical factors that affect pain after transabdominal preperitoneal (TAPP) repair. Methods: We evaluated 199 patients who underwent elective TAPP for inguinal hernia from 2014 to 2019 in Heisei Memorial Hospital. The umbilical trocar size was changed from 12 to 5 mm from October 2017. The pneumoperitoneum intra‐abdominal pressure was changed from 10 to 8 mmHg from 2019. Postoperative pain scores and analgesics were compared between patients who were grouped according to trocar size and intra‐abdominal pressure, as well as 80 patients who received open repair. Results: Patients with a 12 mm trocar had significantly higher pain than open repair patients ( P < .0001). Patients with a 5 mm umbilical trocar and 8 mm Hg intra‐abdominal pressure had significantly lower pain than a 12 mm trocar ( P = .025) and did not significantly differ with pain after open repair. Analgesic use significantly decreased in patients using a 5 mm trocar than 12 mm ( P = .002). Conclusion: Umbilical trocar size and pneumoperitoneum intra‐abdominal pressure were significantly associated with post‐TAPP pain. Using a 5 mm umbilical trocar and 8 mm Hg intra‐abdominal pressure achieved pain levels as comparatively low as open repair.